Protein structure and interactions elucidated with in-cell NMR for different cell cycle phases and in 3D human tissue models - Jan Rynes; Eva Istvankova; Michaela Dzurov Krafcikova; Enrico Luchinat; Letizia Barbieri; Lucia Banci; Kristyna Kamarytova; Tomas Loja; Bohumil Fafilek; Gustavo Rico-Llanos; Pavel Krejci; Libor Macurek; et al. (Communications Biology)
Abstract Most of our knowledge of protein structure and function originates from experiments performed with purified proteins resuspended in dilute, buffered solutions. However, most proteins function in crowded intracellular environments with complex compositions. Significant efforts have been made to develop tools to study proteins in their native cellular settings. Among these tools, in-cell NMR spectroscopy has been the sole technique for characterizing proteins in the intracellular space of living cells at atomic resolution and physiological temperature. Nevertheless, due to technological constraints, in-cell NMR studies have been limited to asynchronous single-cell suspensions, precluding obtaining information on protein behavior in different cellular states. In this study, we present a methodology that allows for obtaining an atomically resolved NMR readout of protein structure and interactions in living human cells synchronized in specific cell cycle phases and within 3D models of human tissue. The described approach opens avenues for investigating how protein structure or drug recognition responds to cell-cell communication or changes in intracellular space composition during transitions among cell cycle phases.